USE OF MOBILE TECHNOLOGY IN BANKING SERVICES - ALIN ISAC (Annals of the University of Petrosani: Economics)
Technology and applications of mobile phones offer many opportunities for businesses, they also presenting a continuous development and new challenges. Although this service is currently viewed with reluctance by customers, banks need to overcome this drawback and understand how this service can be combined with other alternative channels such as social media, to create value for customers. In this paper I presented information about present and perspectives in mobile applications industry, what can a mobile application do in banking, banking mobile applications in Romania, mobile banking applications worldwide.